2019
DOI: 10.3390/cancers11111747
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Levels Control Sensibility toward Cisplatin in Gastric Cancer via the p53-p73/BIK Pathway

Abstract: Gastric cancer (GC) remains a health issue due to the low efficiency of therapies, such as cisplatin. This unsatisfactory situation highlights the necessity of finding factors impacting GC sensibility to therapies. We analyzed the cisplatin pangenomic response in cancer cells and found HDAC4 as a major epigenetic regulator being inhibited. HDAC4 mRNA repression was partly mediated by the cisplatin-induced expression of miR-140. At a functional level, HDAC4 inhibition favored cisplatin cytotoxicity and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
(61 reference statements)
1
30
0
Order By: Relevance
“…The study from Christian Gaiddon's Lab showed that HDAC significantly induces the mRNA and protein levels of TAp73 and p53 on the protein level in gastric cancer cell lines after cisplatin treatment. This leads to the efficient induction of the proapoptotic gene PMAIP1 (NOXA) and BIK [113]. These findings support the key role of TAp73 in eliminating cancer cells in response to cisplatin.…”
Section: Pharmacological Reactivation Of P73supporting
confidence: 66%
“…The study from Christian Gaiddon's Lab showed that HDAC significantly induces the mRNA and protein levels of TAp73 and p53 on the protein level in gastric cancer cell lines after cisplatin treatment. This leads to the efficient induction of the proapoptotic gene PMAIP1 (NOXA) and BIK [113]. These findings support the key role of TAp73 in eliminating cancer cells in response to cisplatin.…”
Section: Pharmacological Reactivation Of P73supporting
confidence: 66%
“…Hence, more selective inhibitors have been developed. For instance, HDAC4 has an elevated expression in GC, and its alteration (mutation or deletion) correlates with a better prognosis [ 343 ]. The inhibition of HDAC4 by small chemicals enhances cisplatin-induced apoptosis in vitro and in vivo.…”
Section: Tp53 a Guardian Against Gastric Cancmentioning
confidence: 99%
“…The study from Christian Gaiddon’s Lab showed that HDAC significantly induces mRNA and protein levels of p73 and protein levels of p53 in gastric cancer cell lines after cisplatin treatment. This leads to the efficient induction of the proapoptotic genes PMAIP 1 ( NOXA ) and BIK [ 113 ]. These findings support the key role of TAp73 in eliminating cancer cells in response to cisplatin and delineate p73 as a vital target of the drug.…”
Section: Structure and Tumor Suppressor Function Of P53 And P73mentioning
confidence: 99%